2022
DOI: 10.3389/fmolb.2022.844973
|View full text |Cite
|
Sign up to set email alerts
|

Modification Patterns of DNA Methylation-Related lncRNAs Regulating Genomic Instability for Improving the Clinical Outcomes and Tumour Microenvironment Characterisation of Lower-Grade Gliomas

Abstract: Background: DNA methylation is an important epigenetic modification that affects genomic instability and regulates gene expression. Long non-coding RNAs (lncRNAs) modulate gene expression by interacting with chromosomal modifications or remodelling factors. It is urgently needed to evaluate the effects of DNA methylation-related lncRNAs (DMlncRNAs) on genome instability and further investigate the mechanism of action of DMlncRNAs in mediating the progression of lower-grade gliomas (LGGs) and their impact on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“… Chen et al (2022) constructed prognostic signatures of N6-methyladenosine-related lncRNAs in gliomas, demonstrating the feasibility of applying prognostic signatures for patients with glioma. Maimaiti et al (2022) analyzed the relationships between clinical outcomes and methylation-related lncRNAs in LGG and the tumor microenvironment, and found that gliomas are characterized by the tumor microenvironment. Liu X et al (2022) also used m5C-related lncRNAs for prognostic prediction and immune response signature analysis, while Wang et al demonstrated the prognostic value and immune landscape of lncRNAs associated with m6A/m5C/m1A in squamous cell carcinoma of the head and neck.…”
Section: Discussionmentioning
confidence: 99%
“… Chen et al (2022) constructed prognostic signatures of N6-methyladenosine-related lncRNAs in gliomas, demonstrating the feasibility of applying prognostic signatures for patients with glioma. Maimaiti et al (2022) analyzed the relationships between clinical outcomes and methylation-related lncRNAs in LGG and the tumor microenvironment, and found that gliomas are characterized by the tumor microenvironment. Liu X et al (2022) also used m5C-related lncRNAs for prognostic prediction and immune response signature analysis, while Wang et al demonstrated the prognostic value and immune landscape of lncRNAs associated with m6A/m5C/m1A in squamous cell carcinoma of the head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate batch effects, transcriptomic data from the three training datasets, namely GSE54083, GSE75436, and GSE13353, were combined using the "combats" approach in the "sva" package, and principal component analysis (PCA) was used to verify the successful removal of the batch effect. A total of 19 methylation-related genes (MRGs) were annotated based on previous literature, including 3 erasers (TET1, TET2, TET3), 3 writers (DNMT1, DNMT3A, DNMT3B), and 13 readers (UHRF2, MECP2, UNG, TDG, NTHL1, SMUG1,MBD1, MBD2, MBD3, MBD4, ZBTB33, ZBTB38, ZBTB4) [ 34 , 35 ]. The expression of these MRGs between the samples was compared using either the Kruskal–Wallis test or Wilcox test, visualized using the RCircos package to study their chromosomal location, and their protein levels were explored using the STRING database to understand their relationships.…”
Section: Methodsmentioning
confidence: 99%